COST OF PAKISTAN-US RELATIONSHIP AFTER 9/11 - Nousheen Jamshed; Fakhr-ul-Islam (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Pakistan-US cooperation resulted in negative repercussions for Pakistan in strategic, political, economic and social contexts in post-9/11 period. While Pakistan suffers from its worst ever economic, security, and political situation, the U.S. faces considerable domestic pressure in maintaining its support for Pakistan without any apparent benefit to the USA. Pakistan, without any doubt, needs U.S. support, both for tackling the insurgencies within/without and keeping the country from becoming dysfunctional. There is a need for both Pakistan and the U.S. to revisit their strategies and priorities. Enhancing economic support to Pakistan would not only lift the U.S. image within Pakistan but also curb extremism and bring stability in the region.